Styrex - Amis, Monnaliz; Balucan, John Paul.; Serina, Carmela (Diliman, Quezon City College of Engineering, 2002)
This study was done to determine the feasibility of putting up a Polystyrene (Styrofoam) Recycling company utilizing the Limonene Recycling Technology-Styrex Inc. Styrex Inc. shall cater to the polystyrene industry by providing high-quality Polystyrene resin, Styrets, as raw material to the PS manufacturers here in the Philippines at a lower cost. The marketability, profitability and technical and economical viability of the said proposal was evaluated within a time frame of five years by conducting a series of studies included in this paper. The Market Study showed that there is an existing demand for the product, currently not being served by the existing supply of PS resin. This conclusion was supported by a marketing budget intended to further boost the market demand for the next five years. The technical aspect of the recycling process and PS resin production was discussed in the Technical Study. The Limonene recycling technology from Japan will be adapted in the Philippine setting to facilitate production of high-quality PS resin by exploiting the similarity in the molecular structure of PS and Limonene. The equipment and preliminary investment required in this venture was found to be approximately P68 million pesos. This initial cost was then combined with the operational expenditures totaling to three million pesos in the Financial study conducted. The Financial study also illustrated the results of the profitability and sensitivity tests where Styrex Inc. was described to be a viable venture to partake, with a highly positive net present value of P75 million and a rate of return of 20%. The environmental-friendly nature of this project resulted to a complacent outcome in the Social Profitability Analysis. however, the extended payback period of 9.0 years attested the capital intensiveness of this project.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Thermoplastics--Recycling.; Styrene; Participatory monitoring and evaluation (Project management)